Self-Awareness, Attitudes, and Social Norms Toward Sexual Violence Behavior in Educational Settings - Bayu Sekar Larasati; Fixi Intansari (Dinasti International Journal of Education Management And Social Science, 2025)
Sexual violence is an act of insulting, degrading, assaulting, or other actions targeting a person's body and sexual desires through intimidation, contrary to their will, forcing the person to comply due to power or gender inequality, leading to physical, psychological, and sexual suffering. The purpose of this study is to analyze the influence of self-awareness, attitudes, and social norms on sexual violence behavior in educational settings. This research employs a quantitative method with multiple linear regression analysis techniques. The study population includes lecturers and educational staff from three universities in Pringsewu Regency, Lampung, with a total of 110 respondents. The data collection technique used in this study is non-probability sampling with convenience sampling. The results show that the significance coefficient of self-awareness, attitudes, and social norms toward sexual violence behavior is 0.004 (p ? 0.01). Based on the findings, it is concluded that self-awareness, attitudes, and social norms have an influence on sexual violence behavior in educational settings. The obtained R-square value is 0.117 (11.7%), indicating that self-awareness, attitudes, and social norms contribute 11.7% to sexual violence behavior, while the remaining 89.3% may be influenced by other variables not examined in this study.